2008
DOI: 10.1088/0022-3727/41/19/195108
|View full text |Cite
|
Sign up to set email alerts
|

Nano-vanadium oxide thin films in mixed phase for microbolometer applications

Abstract: Among the several phases of vanadium oxide, mixed phases of VO2 and V2O5 are preferred for uncooled micro-bolometers with low noise. The aim of this investigation is to achieve mixed phase VO2 and V2O5 thin films with nanometre grain sizes and high temperature coefficient of resistance (TCR). Since the phase depends upon the oxygen reactivity, these vanadium oxide thin films are prepared by reactive electron beam evaporation at different oxygen flow rates and substrate temperatures. The mixed phases have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…The V 2 O 5 phase also has high TCR but its resistivity is too high (> 1 × 10 4 · cm). Thus, mixed VO x thin films may be suitable due to their big resistivity range (0.01∼10 · cm) and high TCR [4]. The relationship between resistivity and TCR is generally subject to the specific composition of the film, especially to the content of oxygen (O).…”
Section: Introductionmentioning
confidence: 99%
“…The V 2 O 5 phase also has high TCR but its resistivity is too high (> 1 × 10 4 · cm). Thus, mixed VO x thin films may be suitable due to their big resistivity range (0.01∼10 · cm) and high TCR [4]. The relationship between resistivity and TCR is generally subject to the specific composition of the film, especially to the content of oxygen (O).…”
Section: Introductionmentioning
confidence: 99%
“…The typical phases are known as VO, V 2 O 3 , VO 2 (or V 2 O 4 ) and V 2 O 5 (or as a "mixed oxide) (Subrahmanyam et al, 2008 Thus, a mixed phase of VO 2 and V 2 O 5 may demonstrate an appropriate resistivity which is convenient and matches also with the readout electronics for high sensitive bolometers (Malyarov, 1999).…”
Section: Vanadium Oxidementioning
confidence: 99%
“…In general, typical bolometer films using VO x film show semiconductor behaviors in electronic property and therefore TCR value was limited to around 3.0%/°C . 16), 17) In contrast, the TCR value was drastically improved by using the non-hysteretic MI transition region, which was induced by metal-ion-substitutive structural defects. It was revealed that Ti and Nb ions were appropriate ions for inducing structural defects in VO 2 because these ions did not affect the MI transition temperature significantly.…”
Section: +mentioning
confidence: 99%